Evaluating the effect of state aid to business by multicriteria methods - Ginevičius, Romualdas; Podvezko, Valentinas; Bruzgė, Šarūnas (Journal of Business Economics and Management, 2008)
One of the forms of state intervention in market development is state aid (subsidies) to private sector enterprises. Over the period of 2004–2006, a great part of the EU aid was granted to business in Lithuania through the EU structural funds. State aid is a complicated phenomenon. It may have several aims, with none of them being dominant. The effects of this aid may also be varied and hardly described by a single criterion or indicator. Therefore, multiple criteria evaluation methods can be used to compare the aid to various businesses and to determine its effect on their development objectively. The analysis of state subsidies to enterprises based on these methods allowed us to state that the aid had the greatest effect on the development of projects in the areas of production, research, experiments and education. The most influencing factor is aid intensity (the more intensive the aid, the greater the effect), while the best ratios of investments to the effect obtained was found in the area of educational projects, followed by research, experimental and production projects. The aid to enterprises providing services was the least effective. The results obtained in multicriteria evaluation of state aid to business show that these methods are well suited to the analysis of this phenomenon, providing an objective view of the picture.First published online: 14 Oct 2010